Virtual teams: a new opportunity to develop a business - Ale Ebrahim, N.; Ahmed, S.; Abdul Rashid, S.H.; Taha , Z. (2010)
Virtual teams give many advantages to organizations, including increased knowledge sharing and improve organizational performance. Virtual teams have altered the expectations and boundaries of knowledge worker’s interactions and make a new opportunity to develop the business. In this paper, we present summary results of an online survey. The online questionnaire was emailed by using a simple random sampling method to 356 Malaysian manufacturing small and medium –sized Enterprises (SMEs). The findings of this study show that SMEs in Malaysia are gaining to use virtual teams, and it can be concluded that virtual teams provide a new platform for developing the business in SMEs. Based on the study, we suggest avenues for future research that are important to advancing our understanding of virtual team effects on business growth.